Market power of German food and beverage industries on international markets - Thomas Glauben; Jens-Peter Loy (Kiel University, Department of Food Economics and Consumption Studies, 2000)
In this paper the existence and magnitude of market power for German beer, cocoa powder, chocolate, and sugar confectionary exporters are tested. Two theoretical approaches are employed, the 'pricing of market' (PTM) and the 'residual demand elasticity' (RDE) approach. Even though all markets show a significant violation of the 'law of one price' estimations for monthly data from 1991 to 1998 reveal that markets are in most cases perfectly competitive. However, while in some cases significant market power is indicated for the PTM approach, the RDE results do not support these findings. This leads to the conclusion that the underlying theoretical models fail to consistently match the observed price equilibria on the market under study.
Keywords: 330; Nahrungsmittelgewerbe; Export; Marktmacht; Außenhandelspreis; Betriebliche Preispolitik; Schätzung; Theorie; Deutschland; Welt